Creativity and academic activism : instituting cultural studies - Morris, Meaghan; Hjort, Mette (Duke University Press ; Hong Kong University Press, 2012)
This work explores in detail how innovative academic activism can transform our everyday workplaces in contexts of considerable adversity. Personal essays by prominent scholars provide critical reflections on their institution-building triumphs and setbacks across a range of cultural institutions. Often adopting narrative approaches, the contributors examine how effective programmes and activities are built in varying local and national contexts within a common global regime of university management policy. Here they share experiences based on developing new undergraduate degrees, setting up r.